3D printed controllable microporous scaffolds support embryonic development in vitro. Issue 8 (14th June 2022) - Guo, Jia; Li, Yuanyuan; Gao, Zili; Lyu, Jiawei; Liu, Wenli; Duan, Yongchao; Zhou, Lixun; Gu, Qi
Abstract: Little is known about the complex molecular and cellular events occurring during implantation, which represents a critical step for pregnancy. The conventional 2D culture could not support postimplantation embryos' normal development, and 3D conditions shed light into the "black box". 3D printing technology has been widely used in recapitulating the structure and function of native tissues in vitro. Here, we 3D printed anisotropic microporous scaffolds to culture embryos by manipulating the advancing angle between printed layers, which affected embryo development. The 30° and 60° scaffolds promote embryo development with moderate embryo‐scaffold attachments. T‐positive cells and FOXA2‐positive cells were observed to appear in the posterior region of the embryo and migrated to the anterior region of the embryo on day 7. These findings demonstrate a 3D printed stand that supports embryonic development in vitro and the critical role of 3D architecture for embryo implantation, in which additive manufacturing is a versatile tool.